Effect of Five A Model Self-management on Quality of Life in Patients with Breast Cancer - Marya Kalhor; Mohammad Fathi; Bayazid Ghaderi; Daem Roshani; Shadi Ozairi; Kourosh Rashidi (Hamadan University of Medical Sciences, 2019)
Introduction: Applying group counseling and patient education can improve the quality of life of women with cancer. The purpose of this study was to determine the effect of applying a self-management model on the quality of life of patients with breast cancer referring to Tohid Hospital in Sanandaj in 2017. Methods: In this clinical trial, 90 patients with breast cancer were selected by available sampling method and randomly assigned to intervention (n=45) and control (n = 45) group. Demographic and A QLQ-C30 questionnaires (quality of life for cancer patients) were used for data collection. After completing the questionnaires by both groups, for the patients in the experimental group, a five-year self-management program was conducted in 5 stages for three months. For patients in the routine nursing care control group. Then, the questionnaires were completed by both groups three months after the intervention. Data were analyzed by SPSS 21 and descriptive statistics, pair t-test and independent t-test. Results: There was a significant difference between the quality of life of the patients before and after the intervention. Also, there was a significant difference between the quality of life of the patients in the control group and the post-intervention group (P<0.05). Conclusion: According to the results of this study, it seems that the application of the five A self-management model can improve the quality of life of cancer patients. Therefore, this model can be used as an optimal nursing intervention.